PENERAPAN STARTEGI PEMBELAJARAN BENAR SALAH BERANTAI UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA MATERI PERJUANGAN MEMPERTAHANKAN KEMERDERKAAN SISWA KELAS V SD NEGERI 157 PEKANBARU - Wan Arniati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low learning outcomes of IPS students of class V SD Negeri 157 Pekanbaru.This study aims to find out the results of IPS learning on the material struggle to maintain the independence ofIndonesia students of class V SD Negeri 157 Pekanbaru with the application of the implementation of truelearning wrong chain. The subjects of this study are the students of class V SDN 157 Pekanbaru which amountedto 27 people. This research is a classroom action research. The instrument of this research consisted ofperformance instrument and data collection instrument in the form of observation sheet of teacher activity andstudent activity. Based on the results of research and discussion can be concluded that the students' learningoutcomes in the subjects of social studies, before the action of student learning outcomes pertained not yetcompleted or not succeed, with complete completeness of the classical students is 41%, or only 11, after appliedcooperative learning strategy type correct wrong chain of students who completed in the first cycle increasedcompared to before the action, but the cycle I also can not be said to work, because the complete completenessof classical students is 67%, or 18 students are complete, the second cycle student learning outcomes increasedwith classical completeness 89% , meaning research can be said successful.